Empirical analysis of tourists’ intentions regarding food waste in Serbian hotel industry - Glišić, Slobodan; Stamenković, Predrag (Hotel and Tourism Management, 2025)
Purpose – Food waste management is becoming an increasingly significant global challenge, especially in the hospitality industry, where large amounts of waste are generated, leading to negative environmental, social and economic consequences. This research explores how tourists perceive food waste in Serbian hotels, aiming to uncover the main psychological drivers that influence their intentions to minimize such waste. Methodology – The study uses an adapted Norm Activation Model (NAM) to analyze the effects of awareness of the consequences of food waste, sense of responsibility and personal norms regarding tourists’ intentions. Results – The results indicate that these factors significantly contribute to shaping sustainable behavior, with awareness of the consequences being the most critical. Implications – Incorporating psychological insights into food waste strategies, as suggested by the findings, could serve as a catalyst for implementing sustainable measures in hospitality services.